2013
DOI: 10.1111/phpp.12072
|View full text |Cite
|
Sign up to set email alerts
|

Psoralen–narrowband UVB phototherapy for the treatment of vitiligo in comparison to narrowband UVB alone

Abstract: Addition of psoralen increased the extent of repigmentation due to NBUVB therapy in vitiligo. Further studies are required to determine the long-term efficacy and safety of P-NBUVB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 19 publications
3
32
1
Order By: Relevance
“…Their results showed that the extent of repigmentation in the P‐NBUVB group was significantly higher in the face and neck as well as hands, compared with NBUVB group. The difference was significant even after removing sunlight as a confounding factor . These results are compatible with our findings.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Their results showed that the extent of repigmentation in the P‐NBUVB group was significantly higher in the face and neck as well as hands, compared with NBUVB group. The difference was significant even after removing sunlight as a confounding factor . These results are compatible with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with the study by Bansal and colleagues, in which four patients in the NBUVB group and 10 patients in the P‐NBUVB group had side effects, but the difference was not significant. Nine of 10 patients in the P‐NBUVB group had nausea after taking the psoralen tablet and one of them suffered from phototoxic reactions . In contrast, El‐Mofty and colleagues found the rate of phototoxic reactions to be significantly higher in the P‐NBUVB side of the body, compared to the other side that received NBUVB when psoralen was not taken …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…UVR has both positive and negative effects on human health. It is responsible for the biosynthesis of vitamin D 3 , can stimulate the production of photoprotective melanin (2)(3)(4)(5), and is used therapeutically to treat inflammatory skin diseases, such as psoriasis, vitiligo, localized scleroderma, and atopic dermatitis (6)(7)(8). At the same time, UVR has many negative effects, most notably that it is directly absorbed by cellular DNA, resulting in cyclobutane pyrimidine dimer (CBPD) mutations that can lead to carcinogenesis of resident epithelial cells.…”
mentioning
confidence: 99%
“…A number of clinical studies have been conducted all over the world and all of these studies have documented a positive effect of narrow-band UVB therapy in vitiligo [6, 10, 11]. …”
Section: Discussionmentioning
confidence: 99%